Relationship of private business density with poverty, higher education and technological connectivity in the provinces and districts of Costa Rica. (UNED Research Journal, 2015)
Poverty in Costa Rican has been analyzed from different perspectives for many years, however, the study of current behavior requires innovative approaches. We used detailed official maps to visualize relationships among business density, poverty, higher education and technological connectivity. We found a strong concentration of entrepreneur capacity in the Great Metropolitan Area around the capital, which has more than half of the country’s population in only 4% of the country’s territory. There is no entrepreneurial coordination among provinces and the greatest inequalities occur in the province of Heredia. Areas with less businesses are the poorest in the country and this needs to be addressed by national policies.
Keywords: Business density; poverty; education; higher education